The influencing of extra gelatin catfish’s bone (pangasius hypophthalmus) concerning to the quality of dodol kedondong - Aldi Hafiz Siregar; Suparmi '; Sumarto ' (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2014)
This research was intended to evaluate the influence of catfish bone gelatinon quality of dodol kedondong. The fish bone gelatin was taken from thelaboratory of organic chemistry, Bogor Institute of Agryculture. Four types ofdodol were prepared from a mixture of kedondong (19%), coconut milk (62%),sugar (19%), sticky rice powder (19%) and each dodol was added with 0%, 5%,7% and 9% fish gelatin respectively. The dodol were evaluated for sensoryquality, folding test and proximate composition. The result indicated that dodolfortified with 9% fish bone gelatin was the best in quality. Moisture, ash, fat andfolding test of the dodol was 19,88%, 1,36%, 4,45% and 4,29% respectively.Keywords: Pangasius hypophthalmus, gelatin, catfish bone, dodol